Application of the HRE-S to 140 horses with trigeminal-mediated headshaking and the association of clinical signs with diagnosis, therapy, and outcome - Kloock, Tanja; Hellige, Maren; Kloock, Anke; Feige, Karsten; Niebuhr, Tobias (Frontiers in Veterinary Science, 2024)
Background Horses with trigeminal-mediated headshaking (TMHS) exhibit different headshaking patterns (HSPs), electric shock-like jerking, signs of nasal irritation, and painful facial expressions. The History Rest and Exercise Score (HRE-S) was developed to objectively clarify the severity of the condition in affected horses. This score considers the history and severity of clinical signs at rest and exercise. This study aimed to assess the frequency of different clinical signs and their individual associations with diagnosis, treatment, and outcome in horses diagnosed with TMHS. The clinical records of horses presented with headshaking (HS) at the Clinic for Horses, University of Veterinary Medicine Hannover, between 2006 and 2021 were assessed retrospectively for clinical signs, diagnosis, and treatment. A total of 140 horses were included in the study. Video recordings were evaluated using the HRE-S and compared to the score described by Talbot. Following discharge, owners were interviewed via telephone about the outcome. Correlations between the presence and severity of clinical signs, diagnosis, and outcome were evaluated. Results The following clinical signs were significantly correlated with a higher HRE-S and grade by Talbot: HS at walk (independently of HSP) (52.9%, 74/140), increased total number of demonstrated HSP (independent of the dominant HSP) (more than one HSP per horse in 91.4%, 128/140), signs of nasal irritation (75.9%, 104/137), painful facial expression (67.8%, 80/118), and electric shock-like jerking (77.5%, 107/138). Diagnosis and outcome do not correlate with the presence of the above-mentioned clinical signs. Conclusion The HRE-S was confirmed as a valid tool to evaluate disease severity in a cohort of 140 horses with HS. Additionally, clinical signs identified as indicators for higher disease severity may have a stronger negative effect on patient welfare, but they do not correlate with diagnosis or outcome.